Equity in Education - Gorard, Stephen. author. aut Link
XI, 199 p.
Keywords: Based on the views of teenagers across Europe and in the Far East, this book argues that we need to reconsider how we judge schools and what they are for. It shows that the treatment of pupils in schools makes more difference to teenagers' views on society, and on what it means to be fair, than it does to differences in attainment. .